2014
DOI: 10.1039/c3cp54221a
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical studies of silver nanoparticles: a guide for experimentalists and a perspective

Abstract: This perspective summarises four different electrochemical techniques that have been established and frequently used to characterize various properties of silver nanoparticles. These are based on drop casting (I), in situ nanoparticle sticking and stripping (II), transfer sticking and stripping (III) or nanoparticle impacts (IV). The specific characteristics of the different methodologies are explained and contrasted with each other with the focus being on the respective benefits and limitations together with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 35 publications
0
40
0
Order By: Relevance
“…Past nano-impact experiments have been conducted mostly in high ionic media and yielded excellent agreement with conventional sizing techniques. [25] Recent work on the coulometric sizing of quasi-spherical NPs has used as upporting electrolyte concentration of 0.10 m and gave good agreement between SEM imaging and coulometric sizing. [19] Lower concentrations of the supporting electrolyte have also been successfully used to characterise smaller (30 nm diameter) Ag particles.…”
Section: Silver Np Characterisationmentioning
confidence: 99%
“…Past nano-impact experiments have been conducted mostly in high ionic media and yielded excellent agreement with conventional sizing techniques. [25] Recent work on the coulometric sizing of quasi-spherical NPs has used as upporting electrolyte concentration of 0.10 m and gave good agreement between SEM imaging and coulometric sizing. [19] Lower concentrations of the supporting electrolyte have also been successfully used to characterise smaller (30 nm diameter) Ag particles.…”
Section: Silver Np Characterisationmentioning
confidence: 99%
“…In addition, care must be taken to minimize agglomeration/aggregation during nanoimpact experiments. Readers interested in experimental aspects of the electrochemistry of particles are directed to the work of Tschulik et al 39 …”
Section: Resultsmentioning
confidence: 99%
“…Understanding the interactions between engineered nano‐objects and interfaces is of particular interest. A few studies reported on detection and analysis of NPs based on their concentration, size, and agglomeration state . Recently, we published a new concept based on nanoparticle‐imprinted matrices (NAIMs) combined with electrochemical detection .…”
Section: Introductionmentioning
confidence: 99%